IMPLEMENTASI TANGGUNG JAWAB KEJAKSAAN NEGERI DALAM PEMBERANTASAN TINDAK PIDANA KORUPSI DI INDONESIA (STUDI FIELD RISET PERPUTAKAAN) - Boby Daniel Simatupang; Edy Kristianta Tarigan (LPPM Universitas Potensi Utama, 2021)
One of the law enforcement agencies that have competence in eradicating criminal acts of corruption is the authority of the Prosecutor's Office. Therefore, a study was conducted on the implementation of the Attorney General's responsibility in handling corruption in order to find out the obstacles and efforts to eradicate corruption eradication. Therefore, this paper discusses